Aerobic Exercise as a Therapeutic Strategy in Children and Adolescents with Metabolic Dysfunction Associated Steatotic Liver Disease (MASLD) and Obesity: A Systematic Review - Nerissa Arviana Fuad; Annisa Alifianti; Nabila Annisa Harum; William Cheng (The Indonesian Society of Pediatric Gastroenterology, Hepatology, and Nutrition, 2025)
Background: Metabolic dysfunction-associated Steatotic Liver Disease (MASLD) is the most prevalent chronic liver disease in children and adolescents, particularly those with obesity. MASLD often progresses to serious hepatic and metabolic complications. Although aerobic exercise (AE) is widely recommended as a first-line lifestyle intervention, its therapeutic efficacy remains unclear. This study evaluates the effects of AE on body composition, liver enzyme, lipid profile, metabolic markers, and liver imaging. Methods: A comprehensive literature search was conducted across PubMed, Cochrane Library, Scopus, and EBSCOhost. Clinical studies involving AE in pediatric patients (≤18 years) with MASLD and BMI ≥ 85th percentile were independently screened. Result: From 141 records, five studies (3 RCT, 2 Interventional Study) involving 97 children (mean age 13.22±2.24 years) met the inclusion criteria. AE protocols typically consisted of 30-60 minutes sessions, thrice weekly, over 1-12 months. AE intervention had significantly decreased BMI in 2 of 3 studies, and visceral fat in 1 of 2, with no change in lean mass. Significant improvements of AST and ALT (Δ –1.0 to –34.0 and –1.0 to –27.17) were reported in 3 of 5 studies. However, lipid profiles showed inconsistent effects, and most metabolic markers (glucose, insulin, HOMA-IR, adiponectin, leptin) showed no significant changes. Liver imaging from 3 studies reported resolution or reduced MASLD severity. Conclusion: AE provides selective benefits in MASLD-obese children and adolescents. Improvements were observed in BMI, liver enzymes, and liver imaging, while the effects on lipid and metabolic markers remain inconsistent.